Growing together : encouraging emotional engagement with communal gardening : an exegesis presented in partial fulfilment of the requirements for the degree of Master of Design, Massey University, College of Creative Arts, Wellington, New Zealand - Shi, Sherry (Massey University, 2018)
Community gardens are open spaces where food or flowers are cultivated, and are managed and operated by members of the local community. Their benefits range from producing food, building community, education and promoting health, to enhancing the resilience of individuals and environments. However, people who have been involved, and who recognise the value of those gardens believe engagement in community gardens is lower than desired. Moreover, there is an age gap of gardening experience: nowadays younger people have less experience growing their own food, while there are not opportunities for experienced older people to pass down their knowledge. Informed by the success of digital services in engaging users, I addressed and delved into my research question: How can the methods and approaches taken from interaction design practice prototype a digital service that encourages emotional engagement in communal gardening? During my research inquiry, I looked to interweave concepts from interaction design, emotional design and gamification; I went through a spiral design process combining deep engagement with potential users, and iterated my design to the final solution presented through an interactive prototype. The final prototype offers an experience through a series of interactions which communicate main scenarios in a user journey. These interactions also illustrate how design can shape a digital service as a “joy maker” and as a “mutual friend”, connecting the two roles in my proposed service: “gardening event host” and “garden bee”.
Keywords: User interfaces (Computer systems) -- Design; Web sites -- Design -- Psychological aspects; Mobile communication systems -- Social aspects; Gamification; Community gardens -- New Zealand